METHODOLOGICAL BASIS OF THE USE OF DIGITAL TECHNOLOGIES IN TEACHING RADIOLOGY IN HIGHER MEDICAL EDUCATIONAL INSTITUTIONS (Universal International Scientific Journal, 2026)
This article discusses the methodological foundations of the use of digitaltechnologies in the process of teaching radiology in higher medical education institutions. The issuesof strengthening students' theoretical knowledge, developing practical skills, and increasing theeffectiveness of independent learning through the introduction of modern information andcommunication technologies into the educational process are analyzed. Also, the pedagogicalpossibilities of using virtual laboratories, simulators, electronic learning platforms, multimediaresources, and programs based on artificial intelligence in teaching radiology are considered. Methodsfor modeling clinical cases, analyzing images, and forming diagnostic decision-making competenciesusing digital technologies are substantiated. The results of the study show that the use of innovativeapproaches in teaching radiology serves to increase the quality of education and student activity. Thiswork contains practical recommendations for improving the digital educational environment in highermedical education institutions and introducing modern pedagogical technologies into the educationalprocess
Keywords: radiology; digital technologies; higher medical education